Resilience as molecular enhancement: bio-economies and medical countermeasures in the United States. Issue 1 (2nd January 2019) - Long, Christopher
ABSTRACT: How have advances in the molecular sciences reshaped our understandings of resilience? This article argues that a novel form of resilience emerges out of the US government's response to the threat of bioterrorism. This response has focused on the development and stockpiling of new pharmaceutical defences known as medical countermeasures. Medical countermeasures allow the body to 'bounce back' from an attack by enhancing at a molecular scale. The obstacles involved in reshaping molecular life into viable countermeasures has led to the creation of a government backed bio-economy formed of public-private partnerships. In doing so, the US government has taken on an extended role accepting the risk that arises in this area. The result is a new scale at which resilience can be implemented and in contrast to many conclusions in the field of International Relations, the responsibilisation of the state rather than citizens in the face of crises.